The e.ffect of simultaneous doping . of Pll in TJ..Q,6 htyer of ’T’lJ-xPb. Ba2Ca2Co_309- o s perconductors
Tn tÂ· p.a,p r We hae reported it;vestigations O:U theÂ· effeot of simtHtaneous sÂ·ubs’tituti9n of :Pb . a;t tbe,1’1-based .IJPercqndl,lctor wasÂ· prepar.d by adcling; an .amounÂ· 0f Pb t. the TIJ-PbxBa;iCa2CuaOo’ti cor:npound. The: usu;d solid’7state teactin meJ;